Centralized distribution system of infusion solutions on a network of health care units (2009)
This document presents a methodology to improve inventory control and distribution policies for a network of hospitals. The strategy is to centralize the management of medicines into a single depot, in order to achieve important cost reduction of the logistic activities involved. On a first stage, a methodology to find near optimal inventory control policies for the one -warehouse, n-retailer distribution system is presented. A Markov Chain model is proposed and solved analytically. Results are evaluated on a real case of a university hospital. On the second stage, a model to decide the location of the new central pharmacy and distribution routes to the set of Care units is proposed. The objective is the minimization of the present value of the project and the minimization of the inventory-on-hand value. The methodology to design the new distribution routes is based on the Clarke & Wright algorithm improved with the local search algorithms.